Pengaruh Pola Asuh Demokratis terhadap Kreativitas Anak usia 4-5 Tahun di TPA Siti Hajar - Nurwila Ye’te; Nurul Aini Mm. Sodik; Salwa Afrillia Patilima; Alia Aziza Sapii; Nahara R Yamudu (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This research at TPA Siti Hajar aims to determine the impact of democratic parenting on the creativity of early childhood aged 4-5 years. The study found that 80% of respondents demonstrated good assessment results, while 20% achieved excellent grades. Democratic parenting, observed in this study, plays a significant role in fostering independence and confidence in children. This type of parenting is ideal for educating children, as it promotes responsibility, leadership, independence, and the ability to build healthy interpersonal relationships. Creativity, as defined in the study, is the ability to generate new ideas, solve problems, and produce innovative products. Using a quantitative approach with an experimental method, the research involved 10 out of 15 children from TPA Siti Hajar. Data was collected through observation and interviews. The results showed a significant correlation between democratic parenting and the development of children's creativity. Children exposed to democratic parenting exhibited increased independence and creativity, adapting well to their school environment. The study concludes that democratic parenting significantly influences early childhood creativity, fostering a safe and supportive space for children to thrive. This positive influence encourages independence while maintaining clear, consistent boundaries, which enhances their creative and developmental stages.